Atypical Crouzon Syndrome With a Novel Cys62Arg Mutation in FGFR2 Presenting With Sagittal Synostosis. - Sharma, V; Wall, SA; Lord, H; Lester, T; Wilkie, A (2012)
The management of a 1-year-old boy with Crouzonoid features is presented with a description of molecular genetic investigations that revealed a previously unreported mutation of the fibroblast growth factor receptor 2 (FGFR2) gene encoding the amino acid substitution p.Cys62Arg within the immunoglobin-like (IgI) domain. The patient presented in atypical fashion with severe sagittal synostosis but only mild exorbitism and hypertelorism. Owing to the progressively increasing size of the cranial occipital bullet, a total calvarial modeling procedure was performed at 8 months of age to correct the craniofacial deformity. Standard genetic testing of the major mutational "hotspots" associated with craniosynostosis was initially negative. However, further testing for atypical sites of mutation revealed a heterozygous nucleotide substitution (c.184T>C) in exon 3 of FGFR2. This mutation has not been previously reported and is only the second to be identified in the IgI domain; it was not present in either parent, indicating that it had arisen de novo. The child remains well 6 months postoperatively but will be monitored more closely compared with the usual protocol for nonsyndromic sagittal synostosis owing to the potential for increased risk of secondary complications. Key learning points from this case include the need for careful phenotypic evaluation of children presenting with apparently isolated sagittal synostosis and genetic testing for atypical mutations if the usual hotspots are negative.